a n b n = a n + 1 a n − 1 − b n + 1 b n − 1 = b n + 1 a n − 1 + a n + 1 b n − 1
Consider, two recursive relations defined as above with initial starting conditions a 0 = 1 , b 0 = 2 , a 1 = 3 and b 1 = 4 .
If the value of a 2 0 1 5 2 + b 2 0 1 5 2 can be expressed as y x , where x , y are coprime integers. Find the value of x + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great observation with the use of the complex number substitution!
Brilliant! Do you have any resources that have more problems of this type?
Problem Loading...
Note Loading...
Set Loading...
Consider,
a n + i b n = a n + 1 a n − 1 + i 2 b n + 1 b n − 1 + i a n + 1 b n − 1 + i b n + 1 a n − 1 a n + i b n = ( a n + 1 + i b n + 1 ) ( a n − 1 + i b n − 1 )
Let S n = a n + i b n
So,
S n = S n + 1 S n − 1 = S n + 1 S n S n − 2 S n + 1 = S n − 2 1 S n = S n − 3 1 = S n − 6
So,
S 2 0 1 5 = S 5 = S 2 1
But since S 1 = S 2 S 0
So,
S 2 = S 0 S 1 = 1 + 2 i 3 + 4 i a 2 0 1 5 2 + b 2 0 1 5 2 = ∣ S 2 0 1 5 ∣ 2 = ∣ S 2 ∣ 2 1 = 5 1
So, x + y = 6 .